Global proteome analyses of phosphorylation and succinylation of barley root proteins in response to phosphate starvation and recovery - Wang, Juncheng; Li, Chengdao; Yao, Lirong; Ma, Zengke; Ren, Panrong; Si, Erjing; Li, Baochun; Meng, Yaxiong; Ma, Xiaole; Yang, Ke; Shang, Xunwu; Wang, Huajun (Frontiers in Plant Science, 2022)
Phosphate (Pi) stress is an important environmental factor that limits plant growth and development. Of various posttranslational modifications (PTMs), protein phosphorylation and succinylation are the two most important PTMs that regulate multiple biological processes in response to Pi stress. However, these PTMs have been investigated individually but their interactions with proteins in response to Pi stress remain poorly understood. In this study, to elucidate the underlying mechanisms of protein phosphorylation and succinylation in response to Pi stress, we performed a global analysis of the barley root phosphorylome and succinylome in Pi starvation and recovery stages, respectively. A total of 3,634 and 884 unique phosphorylated and succinylated proteins, respectively, corresponding to 11,538 and 2,840 phospho- and succinyl-sites, were identified; of these, 275 proteins were found to be simultaneously phosphorylated and succinylated. Gene set enrichment analysis was performed with a Kyoto Encyclopedia of Genes and Genomes pathway database revealing pathways that significantly enriched in the phosphorylome and succinylome. Such pathways, were dynamically regulated by Pi starvation and recovery treatments, and could be partitioned into distinct metabolic processes. In particular, phosphorylated proteins related to purine, the mitogen-activated protein kinase (MAPK) signaling pathway, pyrimidine, and ATP-binding cassette (ABC) transporters were up-regulated in both Pi deprivation and recovery stages. Succinylated proteins, significantly up-regulated by both Pi starvation and recovery, were enriched in nitrogen metabolism and phenylpropanoid biosynthesis. Meanwhile, succinylated proteins that were significantly down-regulated by both Pi starvation and recovery were enriched in lysine degradation and tryptophan metabolism. This highlighted the importance of these metabolic pathways in regulating Pi homeostasis. Furthermore, protein–protein interaction network analyses showed that the response of central metabolic pathways to Pi starvation and recovery was significantly modulated by phosphorylation or succinylation, both individually and together. In addition, we discovered relevant proteins involved in MAPK signaling and phenylpropanoid biosynthetic pathways existing in interactions between phosphorylated and succinylated proteins in response to Pi recovery. The current study not only provides a comprehensive analysis of phosphorylated and succinylated proteins in plant responses to Pi starvation and recovery, but also reveals detailed interactions between phosphorylated and succinylated proteins in barley roots.